PELATIHAN PENYUSUNAN RPP BAHASA INGGRIS DENGAN METODE MONTESSORI BAGI PENGAJAR KB/TK BAITUL MAKMUR - Ahimsa Padmanaba Murfi,; Zulmy Faqihuddin Putera,; Tutuk Widowati,; Umi Anis Ro’isatin,; Henny Purwaningsih, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Language development is an important aspect of early childhood development. This is one of the considerations for many early childhood education institutions, including KB/TK Baitul Makmur, Malang, to teach English to their students. However, the method used has yet to be tested according to the children's natural phase in learning language. This is important to minimize children's difficulties or stress in learning a foreign language. These goals can be achieved by applying the proven Montessori method, and according to the child's cognitive abilities. This workshop aims to enable education practitioners in the kindergarten to develop English learning plans using the Montessori method, especially for children aged 3-6 years